Stories of Change, a structured case study approach which systematically assesses and analyzes drivers of nutritional change in specific country contexts - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
All the case studies, including the Stories of Challenge - focusing on how countries are grappling with the challenge of addressing the obesity epidemic - are now available on a dedicated webpage (https://www.ifpri.org/project/stories-change-nutrition).